Education Program for Strengthening Literacy-Numeracy through 10 in 1 Box Media in Elementary School - Nadiah Putri Anggraeni; Nidya Nur Mashitoh; Tika Widiya Ningrum; Kevin Cahya Andilla Unwaru; Naili Afkarina; Lailatul Nuraini (International Journal of Community Service Learning, 2023)
Education is the provision of knowledge of a particular subject to increase understanding. Numeracy literacy consists of three aspects, namely, counting, numeracy relations, and arithmetic operations. Indonesian students have a low sbility in numeracy literacy. The aim of this community service activity is to analyze the effectiveness of the results of an educational program using 10 in 1 box media with local content to strengthen literacy and numeracy in elementary school students. The service method used is the service learning (SL) approach. The results of the service activities stated that there were differences in literacy learning outcomes before and after the treatment, the average literacy results after the treatment were higher than before the treatment. Sig value. (2-tailed) 0.000 < 0.05, so it can be said that there is a significant difference between before being treated (pretest) and after being treated (posttest). The average n-gain score is 0.7818 > 0.7, meaning the category obtained is a high level of effectiveness. Meanwhile, for the n-gain percentage, the value obtained was 78.18%, so it can be interpreted that the 10 in 1 box educational media for protection culture is effective for enforcement numeracy literacy skills of elementary school student.